2007
DOI: 10.1149/1.2509285
|View full text |Cite
|
Sign up to set email alerts
|

High Conductivity LiFePO[sub 4]∕C Composite Thin Films with Ti Underlayers Deposited by Radio Frequency Sputtering

Abstract: LiFePO 4 /C thin films have been deposited on Ti-coated Si and stainless-steel substrates by radio frequency magnetron sputtering. Negative electric bias ͑0,−50,−80 V͒ and postdeposition vacuum annealing ͑150-650°C͒ was applied to modify the film properties. Suitable substrate bias resulted in films with finer grains and pure olivine phase. The films deposited with Ti underlayers exhibited enhanced crystallization, grain sizes, and conductivity, as compared with films deposited without Ti underlayers. Composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…As a consequence, a layer with LieTi composition forms at the interface which can be observed by the bump in the LiTi þ signal. The observed Ti interdiffusion agrees well with Chiu et al [12].…”
Section: Interdiffusion Behavioursupporting
confidence: 92%
See 2 more Smart Citations
“…As a consequence, a layer with LieTi composition forms at the interface which can be observed by the bump in the LiTi þ signal. The observed Ti interdiffusion agrees well with Chiu et al [12].…”
Section: Interdiffusion Behavioursupporting
confidence: 92%
“…Such a heat treatment can intensify interdiffusion as shown by Chiu et al for LFP thin films on substrates with a titanium interlayer [12]. The effect of interdiffusion between substrate and LFP film was also observed by Legrand et al on MgO substrates [20].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The conventional cathode materials, such as LiCoO 2 , LiMn 2 O 4 , and LiFePO 4 , of lithium/lithium ion batteries are also strong candidates for the cathodes of micro batteries. The minimization of such materials is best achieved by thin film technologies, such as sol-gel (1-3) and sputtering (4)(5)(6) techniques. The thin film cathode materials are characterized by three main categories (7)(8)(9)(10): layered oxides, which are composed of hexagonal close packed oxygen atom networks with lithium and transition metal ions on alternating (111) planes, such as LiCoO 2 , LiNiO 2 and LiCo x Ni 1-x O 2 ; spinels, such as LiMn 2 O 4 , composed of three dimensional octahedral and tetrahedral frameworks; polyanion compounds, such as LiFePO 4 , composed of tetrahedral anion mainframes.…”
Section: Introductionmentioning
confidence: 99%
“…There have been substantial amount of papers regarding preparation of these thin film cathodes. However, most of them showed that post or in-situ high temperature annealing is inevitable in order to fabricate well-crystallized thin film cathodes (1)(2)(3)(4)(5)(6)(7)(8). Although amorphous or nano-crystalline thin films were also used as cathode materials (11), they generally exhibit low specific capacity and sloppy discharge plateau, compared with the polycrystalline counterparts.…”
Section: Introductionmentioning
confidence: 99%